Incubadora educacional para a enfermagem: proposta de um programa de inserção de novos colaboradores no atendimento de pacientes graves - Harres, Juliana (Universidade do Vale do Rio dos Sinos, 2014)
The world has witnessed in recent decades a constant movement of changes in technology as a whole, which started in the industry and has expanded into all areas of the service industry. In hospitals this reality, before exclusive to complex care areas, today permeates the continuity of care and demand for highly skilled professionals who can prioritize actions, anticipate and intervene early to prevent any risk to patients. Within this context we created the concept of Educational Incubator for Assistence, which was implanted in 2010, at Hospital Mãe de Deus in Porto Alegre, a large private hospital, aiming to instruct all new nurse employees in care units under a new arrangement, focusing on the specific needs to the each patient healthcare. As the effectiveness results regarding the health care indicators and human resource, the purpose of this study is to propose an inserction methodology of new employees in the adult ICU, taking as reference the existing Educational Incubator in Care Units. The research used a quantitative approach and the outline of the research method used was the evaluation research. To collect data, a questionnaire wih open and closed questions to Education Incubator Graduate employees was applied. After critical analysis os the results, a matrix was formulated as an alternative to insertion of new employees in the adult ICU intervention. This matrix was designed for nurses and nurse technicians, it is approximately 90 days along, divided into three phases. It is expected that a formal and structured training matrix for the insertion of new employees in the adult ICU the quality of care will be increased, producing a continuous learning environment, where employees are the main actors responsible for the pursuit of knowledge and not merely spectators of action. It is suggested to test the model, after a period of at least one year from the matrix, to conduct a comparative of indicators of care quality in the area to demonstrate the efficiency and effectiveness of the program.
Keywords: Educação permanente; Educação em enfermagem; Competência professional; Education nursing; Education continuing; Professional competence; ACCNPQ::Ciências da Saúde::Enfermagem